Le jeu des illusions : discrimination entre apparence et réalité chez les primates - Marie Hirel (Revue de Primatologie)
Perception is an essential process to gather information about our physical and social environment, and thus to adjust our behaviour to environmental changes. However, we are confronted every day with ambiguous situations in which things appear different from what they really are, like with visual illusions. An array of studies highlighted that nonhuman primates and humans share a sensitivity to illusions, but which differs between species depending on patterns and proprieties of visual elements, thus bringing out interspecific differences in perceptual organization of visual stimuli. In addition to being sensitive to, being able to understand when a misperception can lead us to misconstrue our environment, and thus to behave in inappropriate ways, confers an obvious evolutionary advantage. Being able to realize that our perception of environment can differ from reality corresponds to the appearance-reality discrimination ability. Appearance-reality discrimination is important in social context because we can be deceived by the information we receive from individuals or actions in complex social interactions. Thereby, some researchers consider this ability as a prerequisite for the development of a “Theory of Mind”, i.e. the ability to attribute mental states to oneself and to others. Despite its undeniable ecological and social importance in primates, appearance-reality discrimination has only been studied by developmental psychologists, providing valuable information about its development on children. Only recently, four studies have finally been carried out on nonhuman primates and their results demonstrate that these species are able to discriminate appearance from reality. These promising results are a first step in research on the evolutionary origin of appearance-reality discrimination, but our current knowledge on the subject is still lacking. It appears thus necessary to increase the number of studies with other nonhuman primates for bringing new elements on this ability and, more generally, on the evolution of primate cognition.